Kearifan tempatan: Deskripsi dan Terminologi tentang 'Padi' dalam masyarakat Iban di Sarawak - Remmy, Gedat; Rosnah, Mustafa; Hamidah, Abdul Wahab; Wan Robiah, Meor Osman; Siti Marina, Kamil (2017)
Paddy has its own value and unique identity within the Iban community in Sarawak.This community’s high regard and appreciation for rice are manifested in the annual festival to celebrate the rice harvest known as the Gawai Festival. This festival marks the community’s commemoration and worship of the spirit of the paddy because the Ibans believe paddy to be holy and possess a spirit. The supremacy of paddy within the Iban community can be found in the Iban oral tradition, including the story Penti Pemali Muai Leka Asi Pumai Kitai Iban. In the past, a family is considered rich and of 2 hardworking descent if they have a lot of paddy. Today, the values and beliefs in the planting rituals are slowly disappearing. This paper aims to document and explain the terminology associated with paddy and the activities in paddy planting within the Iban community in Sarawak. This study which employed the interview and observation methods found that due to modernisation, a huge number of traditional terms associated with paddy are slowly disappearing from the Iban community. The researchers believe that modernisation may potentially result in the loss of these traditional terms or their relegation to archaic forms of the language by future generations, unless these terms are documented and continue to be used within the community.